The Jump Rope for Heart Project: An Education Programme for Hong Kong School Children : 跳繩樂齊齊學 - 健康敎育計劃 - HA, Amy S.; WONG, Stephen H.; CHAN, Daniel W. (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The primary objectives of this project are twofold: First, to enrich the learning experiences of the Hong Kong school children in health and physical education through a comprehensive rope-jumping programme. Second, to promote and maintain cardiovascular health among the Hong Kong school children through the active participation in rope-jumping activities. The target population for this project will be student of ten primary schools (P.4-P.6) and ten junior secondary schools (S.1 - S.3) in the territories. About 2,500 male and female students aged 9-14 will be included. The project will be implemented between September 1999 and March 2001. Under this project, an educational package including video series and handbooks on nutrition, exercise, and fitness will be developed in assisting school physical educators to promote a healthy lifestyle to their students. By inserting this proposed project into the present physical education curriculum, physical educators will find necessary philosophy, strategies, and pedagogical models to incorporate health and fitness education into a well-balanced school physical education curriculum. All in all, it is most important to develop a comprehensive and quality physical education programme which integrates appropriate physical activities, concepts, and value leading to healthy lives throughout a child's experiences in the home, school and community. 本計劃主要目的為：一. 透過一項綜合性的跳繩活動計劃來增加香港學童在體育敎育方面的學習經驗。二. 通過參與跳繩活動向香港學童推廣保持心肺健康的信息。是項計劃對象為二千五百名年齡介乎九至十四歲之中(中一至中三)，小(小四至小六)學男女學童。計劃於一九九九年九月至二零零一年三月期間進行。為協助學校體育敎師向學生推廣健康生活的意識，此計劃特別設計了一套完備的敎材：包括營養、運動和體適能敎學手冊及錄影帶。